Genetic Diversity of 17 Genotypes of Taro Based on Morphological Characteristics - Cahyanti, Lutfy Ditya; Santosa, Edi; Sopandie, Didy; Purnamawati, Heni (AGRIVITA Journal of Agricultural Science, 2025)
This study aims to identify the morphological characteristics of 17 taro genotypes. The research involved the inventory and morphological identification of taro genotypes in Bogor, West Java Province, and Ponorogo, East Java Province. The morphological description of taro followed the guidelines in the IPGRI descriptor book. Analysis of variance (ANOVA) was used to examine quantitative data. Using the 22-0 version of SPSS Software, Duncan’s multiple range test was employed at a 5% significance level to determine whether the variables observed had a significant effect. A cladogram was created to evaluate the degree of similarity between the taro genotypes based on the collected data. Fourteen genotypes of Colacasia have been identified, consisting of 7 Eddoe types: Satoimo, Ozikawa, Siromi, Jepang Ungu, Dempel, and Dempel Ungu, 7 Dasheen types including Bentul Ungu, Ketan, Pratama, California, Sutra, Pari, and Bentul, while 3 Xanthosoma including Talas hitam, Talas HIjau, and Talas Kuning. The results showed that the highest association coefficient values were found in Pratama with California, Bentul Ungu with Ketan, and Ozikawa with Siromi. The genotypic variance coefficients were high for characters associated with taro's growth and yield, including corm weight, cormel diameter, cormel weight, and plant span.